1996
DOI: 10.1177/0022002796040004002
|View full text |Cite
|
Sign up to set email alerts
|

How Civil Wars End

Abstract: What conditions determine whether a civil war ends in a negotiated settlement or a military victory? The authors address this question by developing an expected utility model of the choice between seeking an immediate settlement or continuing to fight in anticipation of eventual victory. The model implies that the likelihood of a settlement varies with estimates of the probability of winning, the time required to win, the rate at which the costs of conflict accrue, and the payoffs for victory versus settlement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…Several recent studies have explored the relationship between civil war and democratization, and they suggest that inconclusive wars (i.e., wars that do not result in a decisive victory) that are also very costly can lead warring parties to seek a negotiated settlement from which a more inclusive and democratic system can emerge (Wood, 2001; Wantchekon and Neeman, 2002). Earlier works have shown that the longer a civil war lasts, the less likely it is to end in a decisive victory by either side and the more likely it is to end in a negotiated settlement (Mason and Fett, 1996). These findings suggest that negotiated settlements are a way out of war for protagonists locked in a costly and stalemated civil war.…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have explored the relationship between civil war and democratization, and they suggest that inconclusive wars (i.e., wars that do not result in a decisive victory) that are also very costly can lead warring parties to seek a negotiated settlement from which a more inclusive and democratic system can emerge (Wood, 2001; Wantchekon and Neeman, 2002). Earlier works have shown that the longer a civil war lasts, the less likely it is to end in a decisive victory by either side and the more likely it is to end in a negotiated settlement (Mason and Fett, 1996). These findings suggest that negotiated settlements are a way out of war for protagonists locked in a costly and stalemated civil war.…”
Section: Previous Researchmentioning
confidence: 99%
“…High war costs and long duration reduce both sides' estimate of their probability of victory and increase their estimate of the total costs they will have to absorb in order to achieve victory. As such, the higher the costs of conflict, the lower will be their expected payoff from continuing to fight (in anticipation of eventual victory) versus seeking a settlement (Mason and Fett, 1996). War outcomes, on the other hand, largely determine how post‐civil‐war power will be distributed.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…David Mason has been a pioneer in the systematic study of civil wars (Mason 1984; Mason and Krane 1989; Mason and Fett 1996; Mason, Weingarten, and Fett 1999). Caught in the Crossfire: Revolutions, Repression, and the Rational Peasant reflects that experience.…”
mentioning
confidence: 99%